Personality of Children and Classroom Bullying: The Role of Parental Physical and Psychological Aggressio - Syed Afzal Shah (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
Objectives: To explore the impact of parental aggression (physical and psychological) on  classroom bullying and to explore the effect of parental aggression on personality traits viz. neuroticism, extraver-   sion, and agreeableness factors of personality of secondary school students. Method: A survey was conducted in the secondary schools of Mansehra, Abbotabad, and Haripur dis-   tricts of Hazara Division from October, 2013 to March, 2014. A sample of 1438 students was selected to collect data by using three questionnaires.  One  questionnaire  was  about  bullying  while  the  other  was about parental aggression. The third questionnaire was about the big five factors  (BFF)  of  per- sonality and focused on only three factors of personality viz. extraversion, neuroticism, and agreeable-  ness. This questionnaire  was  adopted.  Analysis  of  collected  datawas  done  through  descriptive statistics such as mean, standard deviation, whereas for  the  prediction  of  effect  of  independent  vari- able on dependent variable, multiple regression model using SPSS version 20. Results:  The mean and standard deviation value of physical aggression of parents was (3.96 ± 1.23)   while that of psychological aggression was  (3.97  ±  1.08).  Additionally,  the  education  level  of  father  was negatively correlated with their physical aggression (r= -0.29, a= 0.000) as well as psychological aggression (r=- 0.28, a= 0.000). Similarly, mothers' level of education was significantly negatively cor- related with both physical aggression (r= -0.16, a= 0.000) and psychological aggression (r= -0.14, a= 0.000). The results further indicated that parental physical aggression (b= 0.16, t= 5.20, a= 0.000) positively predicted classroom bullying. Moreover, parental psychological aggression proved as signifi-    cant negative predictor of extraversion (r= -0.067,  a= 0.021), whereas parental psychological aggression demonstrated significant positive predictor of neuroticism (r= 0.106, a= 0.001). Conclusion: A high level of aggression both physical  and  psychological  is  expressed  by  parents  against their adolescent children. Among them, more  educated  parents  use  less  aggression  towards their children. This physical and psychological aggression from parents cause damaging effects on extraversion factor of personality while psychological cause neurotic tendencies in secondary school students.